New individualized strategy instructs cryoballoon energy ablation - Lin, Wei-Dong; Fang, Xian-Hong; Xue, Yu-Mei; Liao, Hong-Tao (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Atrial brillation (AF), as one of the most common cardiac arrhythmias, is associated with significant morbidity and mortality (1). Pulmonary vein isolation (PVI) remains the cornerstone treatment for paroxysmal atrial fibrillation (PAF) (2). The second generation of cryoballoon (CB2, Arctic Front Advance, Medtronic, Inc., MN, USA) has proven high success rate in PVI for patients with PAF (3,4). The “Fire and Ice trial” confirms cryoballoon ablation is equivalent to radiofrequency ablation with respect to ef cacy for the treatment of patients with PAF (5).